Green Tourism: A Strategy for Realizing an Environmentally-Based Wonderful Indonesia - Firman Sinaga; Komang Shanty Muni Parwati; Febianti; Komang Trigita Juliastari; Firlie Lanovia Amir (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
The tourism sector is a fundamental pillar of Indonesia's national economy, contributing crucially to Gross Domestic Product (GDP) growth and job creation. However, amidst the acceleration of tourist arrivals, a serious threat emerges in the form of ecosystem degradation that could erode the identity of "Wonderful Indonesia." This study aims to analyze the implementation strategy of Green Tourism as a vital instrument in realizing sustainable, environmentally-based tourism in Indonesia. Using descriptive qualitative methods and policy analysis, this study explores the synergy between government regulations, the readiness of environmentally friendly infrastructure, and local community involvement in preserving natural assets. The study results indicate that the transition to green tourism is no longer merely an ethical option but a strategic necessity to maintain Indonesia's global competitiveness in the eyes of international tourists who are now highly aware of sustainability issues. Green tourism strategies have proven effective in mitigating the destructive impacts of mass tourism while creating long-term economic value through biodiversity preservation and strengthening local culture. This study recommends stricter integration of green certification policies at the regional level and the use of digital technology to monitor environmental carrying capacity in priority destinations.